Development alternatives: Alternative administration - Dwivedi, O.P.; Henderson, K.M. (1996)
Sketching two "ideal-typical" models of development involving universalised values of: (i) human-needs-centred development, and (ii) sustainable development, the authors examine various existing development models (Liberal Democratic, Capitalist, Communist, Sarvodaya, Islamic Fundamentalist, and Liberation Theology) focusing on their philosophy and application. While attempting a reassessment and future possibilities for some of these models through corresponding alternate models, they suggest a realistic `unity through diversity' concept of development to effectively marshal full potential of human nature, both in its religious and cultural dimensions. - Reproduced
Keywords: Public administration; Development administration